Altered neural dynamics in people who report spontaneous out of body experiences. (February 2019) - Milne, Elizabeth; Dunn, Stephanie; Zhao, Chen; Jones, Myles
Abstract: It has been suggested that individual differences in cortical excitability leading to disruption of the timing and integration of sensory information processing may explain why some people have out of body experiences (OBE) in the absence of any known pathological or psychiatric condition. Here we recorded EEG from people who either had, or had not experienced an OBE in order to investigate the neural dynamics of OBE in the non-clinical population. A screening questionnaire was completed by 551 people, 24% of whom reported having at least one OBE. Participants who were free of any psychiatric or neurological diagnoses, including migraines, were invited to take part in subsequent EEG recording. EEG data were obtained from 19 people who had had an OBE and 20 who had not. Amplitude of the visual P1 ERP deflection and consistency of alpha-band phase locking were significantly reduced in the participants who had had an OBE. We did not find any group differences in resting state power or in visually induced gamma oscillations. These results provide support for the claim that cortical differences, particularly with respect to the timing of visual information processing, may give rise to OBE in clinically healthy individuals. To our knowledge, this study is the first to compare EEG variables obtained from people who have, and have not, had an OBE.